Performance Governance Analysis of the Career Center Information System at Universitas Muhammadiyah Jambi Using COBIT 2019 - Fadila Fitrianisa; Noneng Marthiawati; Kevin Kurniawansyah; Arniwita Arniwita (International Forum of Researchers and Lecturers, 2026)
This study analyzes the governance performance of information systems at the Career Center of Universitas Muhammadiyah Jambi using the COBIT 2019 framework. The primary objective is to evaluate the maturity level of IT governance and provide recommendations to enhance the efficiency and effectiveness of information systems in supporting the institution’s strategic objectives. Data were collected through interviews, observations, and questionnaires involving system users and decision-makers within the Career Center. The findings indicate that several areas require greater attention, particularly Managed IT Changes, Managed Risk, and Managed Operations. These domains are considered critical in improving the management and reliability of the existing information systems. The study also identifies several challenges affecting system performance, including limited system integration, insufficient human resources, and the use of outdated technology. Based on these findings, the research recommends strengthening the organizational structure, improving the competence of human resources, and optimizing IT processes in accordance with COBIT 2019 standards. Implementing these improvements is expected to increase IT governance maturity, enhance service quality for students and alumni, and better support the university’s strategic development goals.